Enhancing Students’ Learning Outcomes through Problem-Based Learning: An Empirical Study in Classroom Contexts - Yunda Assyuro Hanun; Akhmad Asyari; Mimodje Noupeyou Modeste; Kuiliga Dieudonné Armel Nonguierma (Universitas Islam Negeri Mataram, 2026)
This study aims to improve students’ learning outcomes through the implementation of the Problem-Based Learning (PBL) model in Islamic Education (PAI) for seventh-grade students at SMPN 2 Pringgasela. This research employed Classroom Action Research (CAR) consisting of two cycles, each involving planning, implementation, observation, and reflection stages. The study was conducted collaboratively between the teacher and the researcher as an observer. Data were collected using learning outcome tests and observation sheets to assess teacher and student activities. Quantitative analysis was used to determine individual and classical mastery, while qualitative analysis examined the implementation process. The results showed significant improvements across cycles. Classical mastery increased from 60.71% in Cycle I to 89.28% in Cycle II. Teacher activity scores improved from 65.21 to 86.95, and student activity scores rose from 60.86 to 86.95. These findings indicate that the PBL model effectively enhances student learning outcomes and classroom engagement